Performance Analysis of Three Channel Single Pass Heat Exchanger With Flow Divided In Counterclockwise and Unidirectional Flow Configurations - M. Yoki Al Mahir (International Journal of Mechanical Computational and Manufacturing Research, 2021)
The triple concentric pipes heat exchanger is an improved or the repair version of double pipe heat exchanger. The research of triple concentric pipe heat exchanger have enough developed, especially by C.L.Ko dan G.L. Wedekind who have given theoretically and experimentally analysis. This research was conducted to determine the output of temperature of each channel and find out perfomance heat exchanger effectiveness is based on experimentally and theoretically. In this essay, the development is doing with a broader scope of research C.L. Ko and G.L. Wedekind, the experiment have done with C1/Cs ≤ 1 and C1/Cs ≥ 1 in both counter flow and paralel flow configuration aheat exchan ger used according to the size used C.L. Ko and G.L. Wedekind. The result experiment that average effectiveness is ± 60% with the higgest effectiveness is ± 80.4 % in counter flow configuration and the average effectiveness is ± 43.4% with the higgest effectiveness is ± 55.1 % in paralel flow configuration. Theoretically predicted heat exchanger effectiveness are found on the average different of the experiment ± 9,06% in counter flow configuration and 5,67% in paralel flow configuration. The experiment also show different result of optimum point that predicted by C.L.Ko dan G.L. Wedekind.